Tuning the Redox Properties of a Nonheme Iron(III)–Peroxo Complex Binding Redox‐Inactive Zinc Ions by Water Molecules. Issue 30 (19th June 2015) - Lee, Yong‐Min; Bang, Suhee; Yoon, Heejung; Bae, Seong Hee; Hong, Seungwoo; Cho, Kyung‐Bin; Sarangi, Ritimukta; Fukuzumi, Shunichi; Nam, Wonwoo
Abstract Redox‐inactive metal ions play important roles in tuning chemical properties of metal–oxygen intermediates. Herein we report the effect of water molecules on the redox properties of a nonheme iron(III)–peroxo complex binding redox‐inactive metal ions. The coordination of two water molecules to a Zn2+ ion in (TMC)FeIII‐(O2)‐Zn(CF3SO3)2 (1‐Zn2+) decreases the Lewis acidity of the Zn2+ ion, resulting in the decrease of the one‐electron oxidation and reduction potentials of 1‐Zn2+. This further changes the reactivities of 1‐Zn2+ in oxidation and reduction reactions; no reaction occurred upon addition of an oxidant (e.g., cerium(IV) ammonium nitrate (CAN)) to 1‐Zn2+, whereas 1‐Zn2+ coordinating two water molecules, (TMC)FeIII‐(O2)‐Zn(CF3SO3)2‐(OH2)2 [1‐Zn2+‐(OH2)2], releases the O2 unit in the oxidation reaction. In the reduction reactions, 1‐Zn2+ was converted to its corresponding iron(IV)–oxo species upon addition of a reductant (e.g., a ferrocene derivative), whereas such a reaction occurred at a much slower rate in the case of 1‐Zn2+‐(OH2)2. The present results provide the first biomimetic example showing that water molecules at the active sites of metalloenzymes may participate in tuning the redox properties of metal–oxygen intermediates.